NONEXISTENCE OF GLOBAL SOLUTIONS FOR A NONLINEAR DEGENERATE HEAT EQUATION - Quispe Méndez, Teófanes (2009)
In present work, we study the blow-up finite time of solutions to the mixed problem for a type of nonlinear degenerate heat equation with a generalized Lewis function.